PREDIKTABILITAS PENYELESAIAN SENGKETA EKONOMI MELALUI REFORMASI HUKUM: STUDI LITERATUR ATAS HARMONISASI DAN SINKRONISASI REGULASI DEMI MENDORONG IKLIM INVESTASI NASIONAL YANG SEJALAN DENGAN AMANAT KONSTITUSI INDONESIA - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2025)
This study examines the predictability of economic dispute resolution in Indonesia through the perspective of legal reform that focuses on harmonisation and synchronisation of regulations as instruments to support the national investment climate. Legal uncertainty has arisen from overlapping regulations, inconsistencies in implementation, and weak consistency in court and arbitration decisions. These conditions reduce investor confidence and lower the competitiveness of Indonesia's economic law in the global arena. Using a normative legal research approach and literature study, this research analyses the relationship between regulatory harmonisation, legal certainty, and the investment climate in accordance with the mandate of the constitution. The results of the study show that the ability of the Indonesian legal system to provide predictability is highly dependent on the consistency of norms, the professionalism of dispute resolution institutions, and the application of technology as an instrument of legal modernisation. Legal reforms that emphasise the synchronisation and harmonisation of regulations will not only increase legal certainty but also strengthen the legitimacy of investment in Indonesia within the framework of fair and sustainable economic development in accordance with constitutional principles.